Two green bottles, standing on a wall: an environmental assessment of two bottle types - Ivanov, Ivan G.; Hartmann, Dieter (South African Journal of Industrial Engineering, 2016)
Non-renewable resources are becoming scarce and current Global Warming Potential values are rising. In an effort to promote a successful shift towards a ‘greener’ planet, governments worldwide are developing policies (such as carbon taxation) to encourage businesses to contribute to the effort. This study analysed the product carbon footprint of the packaging process for 300 ml glass and 500 ml PET† containers for a South African soft drink manufacturing business. A review of the academic literature revealed that no similar research had been conducted in South Africa. The Greenhouse Gas protocol was used as the basis for the research method. It was found that the 500 ml PET packaging process draws 100 per cent of its cumulative energy demand from purchased electricity (generated by burning coal); therefore, 500 ml PET containers have 4.5 times less global warming potential per hectolitre than 300 ml glass containers, which have 71 per cent of their emissions resulting directly from coal-fired boilers on site. A dynamic model analysis revealed that packaging in larger containers results in a significant reduction in global warming potential per volume for both glass and PET containers.